IMPLEMENTASI HIDUP ORANG BENAR BERDASARKAN MAZMUR 92:1-16 DI KALANGAN JEMAAT GEREJA PANTEKOSTA ISA ALMASIH SE-JAWA BARAT - Martha Mulyani Kurniawan; Hana Suparti; Timotius Sukarna (Sekolah Tinggi Teologi Duta Panisal, 2021)
The diversity of religious people in Indonesia shows how many people recognize God as worthy of worship. All religions teach doctrines that devotees should adhere to. In reality, though, many people profess to be religious but fail to practice the religious teachings that they carry out so much as a wicked person. Even if they do not worship god wholeheartedly, God blesses them. It often makes the congregation feel that the lives of the wicked are more comfortable, while those who live righteously in doing the word of the Lord are walking into a lot of trouble. The purpose of this study is to know the magnitude of the implementation of a righteous person's life, to know which dimension most predominates the implementation of the righteous person, and to know the background category that most determines the implementation of a righteous person's life based on Psalm 92:1-16 among church congregations by the quantitative method. It's a survey method. Research Result: The application of a righteous person's life based on Psalm 92:1-16 in the congregation is surprisingly moderate. The dominant dimension in the application of a righteous person's life based on Psalm 92:1-16 is life for God. The background category of the ones who most determine the lives of the righteous based on Psalm 92:1-16 is education.